FORMULATION DEVELOPMENT OF SUSTAINED RELEASE ANTIULCER DRUG AND STUDY OF PRE-FORMULATION PARAMETERS AND ITS CHARACTERIZATION - Satbir Singh; Dr. Gaikwad Dushyant Dadabhau; Kehar Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The aim of present study was to formulate and developed sustained release tablets of Nizatidine (220 mg) by varying concentration of polymers like chitosan, Kollidon SR and HPMC K100M by wet granulation technique. The pre-formulation parameters were studied like melting point of drug, FTIR study and DSC analysis of drug. Various pre-compression parameters were evaluated like Bulk density, Tapped Density, Carr’ Index, Angle of repose. This study revealed the idea about how the concentration of polymers affects pre-compression parameters of the drug formulation.